(untitled) (Bangladesh Medical Journal, 2016)
Percutaneous nephrolithotomy (PCNL) in patients operated previously for renal stone are thought to pose some difficulties. This study was carried out to compare the outcome of PCNL in patients who had undergone open surgery for renal stone with the outcome in primary patients. This descriptive cross sectional study was conducted in the Department of Urology, Bangabandhu Sheikh Mujib Medical University, Dhaka during the period of Nov 2012 to Oct 2013. Sixty patients with renal stone admitted in urology department were selected of which 30 cases were with recurrent stone having previous open renal stone surgery (group I - study group) and another 30 were primary patients without previous surgery for renal stone disease (group II - control). After PCNL all the patients were followed at one week, one month and three months after procedure. Mean ages of Group I and Group II were 40.90 ± 6.08 years and 44.10 ± 9.91 years respectively. Mean stone size of the respondents in Group I was 2.98 ± 0.65 cm and in Group II was 3.03 ± 0.67 cm. Mean operation time of the respondents in Group I and Group II were 1.50 ± 0.46 and 1.52 ± 0.33 hours respectively. Mean post-operative hospital stay of the respondents in Group I was 3.87 ± 1.13 days and Group II was 3.67 ± 0.60 days. Stone was cleared from 29 (96.7%) patients in Group I and 28 (93.3%) patients in Group II. Mean drop of Haemoglobin level were 0.85 ± 0.55 mg/dl and 0.94 ± 0.52 gm/dl in group I and group II respectively. It was evident from the study that previous open stone surgery does not alter the outcome of subsequent PCNL. Bangladesh Med J. 2016 Jan; 45 (1): 36-39